Student reflections and recollections: Key outcomes of a post-secondary English for Academic Purposes program moved online - Douglas, Scott Roy; Wiebe, Karin (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2025)
As an alternative to standardized testing, English for academic purposes (EAP) programs provide a language development pathway to higher education for students working towards meeting English language proficiency requirements. During the COVID-19 pandemic, these programs moved online; however, the outcomes of that move and the relationship with additional language learning are still to be fully explored. Based on student reflections and recollections, this study identifies key outcomes related to their online EAP program experiences. Nine participants completed an online questionnaire, with three taking part in interviews. Using a qualitative thematic approach, data were coded and gathered into the following themes: academic and interpersonal skills, network creation, language development, and knowledge building. These findings are presented as building blocks in the additional language socialization process and underscore the potential of online teaching and learning along with the importance of holistic and general approaches to EAP curriculum development and program planning.